Logarithmic Helical Design for Reversed Magnetic Field in Magnetoelastic Soft Matters with Giant Current Outputs - Xiaojun Chen; Farid Manshaii; Dianyu Tang; Yizhuo Xu; Zhuofan Li; Manhui Chen; Peng Chen; Yike Li; Shanfei Zhang; Lei Yang; Jun Chen; Bin Su (Advanced Science)
Abstract Magnetoelastic soft materials are widely used in soft bioelectronics. However, mechanical deformation usually induces minimal changes in magnetic flux, limiting electrical outputs. To overcome this limitation, a two‐step process is employed to enhance the variation in magnetic flux density under mechanical force. On one hand, the helical structural design enables the magnetic membrane to flip completely, reversing the magnetic field. On the other hand, the applied mechanical force induces strain within the magnetoelastic membrane, leading to variations in magnetic flux density. A complete 180° reversal of the magnetic field is achieved using a logarithmic helical structure, resulting in a 200% increase in magnetic flux variation and a peak current of 6.34 mA. Following structural optimization, the current density reached an impressive 7.17 mA cm−2. Using this rationally designed logarithmic helix model, a knee pad is developed for wearable energy harvesting from human body movement. The device can generate a current of up to 2.83 mA, providing sufficient power for various small electronics, including smartphones, LED lights, headlamps, and rechargeable batteries. This achievement represents a significant milestone in advancing high‐performance wearable biomechanical energy harvesting.